Molecular characterization of two begomoviruses infecting Pavonia sp. (Malvaceae), and analysis of the intra-host evolution of Tomato severe rugose virus (ToSRV) - Pinto, Vitor Batista (2015)
The family Geminiviridae is comprised of viruses with a circular, single-stranded DNA genome encapsidated in twinned icosahedral particles. The viruses in the genus Begomovirus are transmitted by the whitefly Bemisia tabaci to dicot plants. Begomoviruses have mutation and nucleotide substitution rates similar to those reported for RNA viruses, and a high frequency of recombination. Due to their rapid evolutionary process, new begomovirus species are often found in the field. This study aimed to perform the molecular characterization of two begomovirus species infecting Pavonia sp. (Malvaceae), and to follow and quantify the evolution of Tomato severe rugose virus (ToSRV) in a cultivated and a non-cultivated host. Two begomoviruses were isolates from Pavonia sp. plants collected in the municipalities of Albuquerque and Corumbá, Mato Groso do Sul, Brazil. Sequence comparisons and phylogenetic analysis showed that these were two novels species, with the typical features of bipartite, New World begomoviruses. The names Pavonia mosaic virus (PavMV) and Pavonia yellow mosaic virus (PavYMV) were proposed for the two new species. In the study to evaluate the evolutionary dynamics of ToSRV, tomato and Nicandra physaloides plants were inoculated via biobalistics with an infectious clone of ToSRV and maintained in a greenhouse. Total DNA was extrated from leaves collected at 30, 75 and 120 days after inoculation, and was sequenced in the Illumina HiSeq 2000 platform. The DNA libraries from each of the two hosts were submitted to quality control analysis with FastQC software. The genome assembly was performed with the program Geneious using the infectious clone as reference. Both genomic components of ToSRV showed substitution rates similar to those of RNA viruses: 3.06 x 10-3 and 2.03 x 10-3 sub/site/year for the DNA-A and DNA-B, respectively, in N. physaloides, and 1.38 x 10-3 and 8.68 x 10-4 sub/site/year for the DNA-A and DNA-B, respectively, in tomato. Substitution rates in the range of those already described for other begomoviruses were found also for the CP, Rep, MP and NSP genes in both hosts. We quantified synonymous and non-synonymous substitutions, transversions and transitions, as well as deletions and insertions in the CP, Rep, MP and NSP genes. A decrease in the number of variable sites was observed during the course of the experiment, with a corresponding increase in the number of identical sites to the reference genome. Suppression of the stop codons of the MP and NSP genes was observed in the N. physaloides libraries, suggesting an adaptive strategy. Determination of Shannon entropy indicated mutation hotspots in the N-terminal region of the Rep gene, the intergenic common region in the DNA-A and DNA-B (CR-A and CR-B, respectively) and the long intergenic region between the MP and NSP genes in the DNA-B (LIR-B). Overall, the results indicate that ToSRV evolves as a quasispecies, with a high degree of genetic variability which could be partly responsible for its prevalence in the field.